2020
DOI: 10.3390/catal10050536
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalysis of Industrial Kraft Pulps: Similarities and Differences between Hardwood and Softwood Pulps in Hydrolysis by Enzyme Complex of Penicillium verruculosum

Abstract: Kraft pulp enzymatic hydrolysis is a promising method of woody biomass bioconversion. The influence of composition and structure of kraft fibers on their hydrolysis efficiency was evaluated while using four substrates, unbleached hardwood pulp (UHP), unbleached softwood pulp (USP), bleached hardwood pulp (BHP), and bleached softwood pulp (BSP). Hydrolysis was carried out with Penicillium verruculosum enzyme complex at a dosage of 10 filter paper units (FPU)/g pulp. The changes in fiber morphology and structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…The hardwood pulp was also evaluated in laboratory refining trials using a PFI mill, showing a similar trend, resulting in EndoC and the commercial endoglucanase formulation FiberCare R leading to the highest degree of refining values when dosed at an identical activity on the derivatized cellopentaose substrate CellG5 (Nagl et al 2021). The softwood pulp also expressed a high level of bends and twists, which were not present when compared to the hardwood pulp, a similar observation was already reported earlier (Aksenov et al 2020). Another factor for varying enzyme performance between the softwood and hardwood pulp is the amount of hemicellulose, which was determined with NMR to be 6.6% for the softwood and 12.3% for the hardwood pulp.…”
Section: Release Of Reducing Sugars From Softwood and Hardwood Pulpsupporting
confidence: 76%
See 1 more Smart Citation
“…The hardwood pulp was also evaluated in laboratory refining trials using a PFI mill, showing a similar trend, resulting in EndoC and the commercial endoglucanase formulation FiberCare R leading to the highest degree of refining values when dosed at an identical activity on the derivatized cellopentaose substrate CellG5 (Nagl et al 2021). The softwood pulp also expressed a high level of bends and twists, which were not present when compared to the hardwood pulp, a similar observation was already reported earlier (Aksenov et al 2020). Another factor for varying enzyme performance between the softwood and hardwood pulp is the amount of hemicellulose, which was determined with NMR to be 6.6% for the softwood and 12.3% for the hardwood pulp.…”
Section: Release Of Reducing Sugars From Softwood and Hardwood Pulpsupporting
confidence: 76%
“…This was also expressed in the crystallinity index, which remained constant or improved only marginally for all observed endoglucanases. This may be attributed to differences between softwood and hardwood pulps like softwood pulps having bends and twists as well as studies showing a different mode of action for softwood pulps leading to fragmentation and increased fiber shortening for softwood pulps (Arantes et al 2014;Aksenov et al 2020). However, the crystallinity index is not always the appropriate measure to assess suitability of the enzymes, which was also suggested by studies dealing with its interpretation and it was found that with progressed hydrolysis, extensive changes to the fiber structure are occurring, making it impossible to attribute changes to the crystallinity index alone (Park et al 2010;Novy et al 2019).…”
Section: Quantification Of the Fluorescent Colour Intensitymentioning
confidence: 99%
“…The convertibility of newer dry as well as dried kraft fibers representing by bleached and unbleached soft wood and hardwood pulp was evaluated (Table 1). The highest convertibility was demonstrated by wet bleached softwood pulp, at 78%; the reason for the high convertibility is the almost complete removal of lignin by the Kraft process (a remaining lignin content was 2-3% [33]). The convertibility of wet bleached hardwood pulp was 58%; this is lower compared with bleached softwood pulp because of the xylan influence [33].…”
Section: Resultsmentioning
confidence: 99%
“…The highest convertibility was demonstrated by wet bleached softwood pulp, at 78%; the reason for the high convertibility is the almost complete removal of lignin by the Kraft process (a remaining lignin content was 2-3% [33]). The convertibility of wet bleached hardwood pulp was 58%; this is lower compared with bleached softwood pulp because of the xylan influence [33]. Unbleached wet softwood and hardwood pulp had approximately a 1.1 times lower convertibility compared with similar types of bleached pulp; the decrease in convertibility of unbleached pulp is explained by the higher lignin content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation